Effect of R Angle of the Outer Extension Tube against the in-Core Flux Thimble in Nuclear Power Plant on Its Wear Behavior - Qiang Chen (Hindawi-Wiley, 2021)
Wear failure of the in-core flux thimble is an important problem in the neutron flux measurement system, which threatens the safety of the nuclear power plant. To figure out the wear mechanism of the thimble, a wear tester was designed and manufactured to simulate the wear process of the in-core flux thimble. Outer guide tubes with different R angles were used to abrade the thimbles. The designed tester can well simulate the wear process in the real power plant. R angle of the outer guide tube played important role in the wear behavior of the in-core flux thimbles.